2017
DOI: 10.1111/eci.12801
|View full text |Cite
|
Sign up to set email alerts
|

Talking the talk, but not walking the walk: RT-qPCR as a paradigm for the lack of reproducibility in molecular research

Abstract: Poorly executed and inadequately reported molecular measurement methods are amongst the causes underlying the lack of reproducibility of much biomedical research. Although several high impact factor journals have acknowledged their past failure to scrutinise adequately the technical soundness of manuscripts, there is a perplexing reluctance to implement basic corrective measures. The reverse transcription real-time quantitative PCR (RT-qPCR) is probably the most straightforward measurement technique available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 161 publications
0
98
0
Order By: Relevance
“…Given the significance of empirical validation, it is important that any publication include that essential information [8] , [9] , [10] , [11] . Several reports have been published recently that together scored thousands of peer-reviewed papers in a wide collection of journals ranging from low to high impact factors [12] , [13] , [14] , [15] , [16] , [17] . All concluded that the amount of critical information provided with papers reporting qPCR data is inadequate for the purpose of evaluating the validity of conclusions arising from those data, with many not reporting primer sequences, validation data or including wrong information.…”
Section: Introductionmentioning
confidence: 99%
“…Given the significance of empirical validation, it is important that any publication include that essential information [8] , [9] , [10] , [11] . Several reports have been published recently that together scored thousands of peer-reviewed papers in a wide collection of journals ranging from low to high impact factors [12] , [13] , [14] , [15] , [16] , [17] . All concluded that the amount of critical information provided with papers reporting qPCR data is inadequate for the purpose of evaluating the validity of conclusions arising from those data, with many not reporting primer sequences, validation data or including wrong information.…”
Section: Introductionmentioning
confidence: 99%
“…We show that the analytical sensitivity of our assay is to the level of single cell RNA detection for relatively highly expressed RPL13a. Sample concentration and clean-up has been suggested to remove inhibitors and increase sensitivity (63,64). Unexpectedly, we found this step did not improve our analytical sensitivity, and was timeconsuming, expensive and reduced sample volume.…”
Section: Discussionmentioning
confidence: 80%
“…In a recent review about the use of RT-Q-PCR, Bustin and Nolan (Bustin & Nolan, 2017) stated that "the majority of published RT-Q-PCR data are likely to represent technical noise".…”
Section: Discussionmentioning
confidence: 99%